Analysing Sino-European Relations through Different Editions of The History of the Great and Mighty Kingdom of China by Juan González de Mendoza - Bo, Gao (Sinología hispánica. China Studies Review, 2026)
For five centuries, The History of the Great and Mighty Kingdom of China by Juan González de Mendoza has had a major influence on the international academic community. Each edition of Mendoza’s book offers an updated interpretation of the contemporary process of Sino-Western relations. This study sets out to explore the process through which the book was translated into Chinese, tracing its source texts and analyzing the isomorphism between different editions and the influence of Sino-Western relations in different contexts.